Resolução CSMPF nº 59, de 12 de junho de 2000 - Haroldo Ferraz da Nobrega; Antonio Fernando Barros e Silva de Souza; Delza Curvello Rocha; Paulo da Rocha Campos; Roberto Monteiro Gurgel Santos; Wagner de Castro Mathias Netto; Helenita Amelia Caiado de Acioli; Sandra Veronica Cureau; Gilda Pereira de Carvalho Berger (DJ, Brasília, DF, 5 ago. 2000. Seção 1, p. 35., 2000)
Altera o art. 18, da Resolução CSMPF nº 1, de 26 de agosto de 1993.